A REVIEW ON EFFECTIVE TEACHING AND LEARNING IN HIGHER EDUCATION - Tilda Karkour Akiki (European Scientific Journal, ESJ, 2014)
This paper provides a review of some approaches for developing teaching and learning in Higher Education institutions. The purpose of these approaches is to explore new techniques for integration and exploitation in order to preserve the good quality of our teaching and to enhance the quality of our students‘ learning experience. New challenges are facing teaching and learning in Higher Education (HE) nowadays and a new framework is established for the success of the student‘s learning experience. With time passing, different theories have evolved like behaviourism, cognitivism, constructivism, and humanism. Behaviourist theories state ―that language is a set of habits that can be acquired by means of conditioning‖. Cognitive theories consider ―learning as an internal mental process‖ and the educator ―structures content of learning activities to focus on building intelligence‖. The purpose of Constructivist theories in education is ―to become creative and innovative through analysis and synthesis of prior experience to create new knowledge‖. The educator‘s role is ―to mentor the learner‖. Humanist theories are ―a paradigm that emerged in the 1960s which focus on the human freedom, dignity, and potential‖.